Resultados de citologias de ânus em mulheres portadoras da infeção genital pelo papilomavírus humano (HPV) - Morais Sobrinho, Nalim Barreto (2019)
Introduction: Anal cancer is uncommon, but its incidence has been increasing in the last 30 years, both in the United States and in other parts of the world. In addition to anal cytological examination in patients with anus lesions, patients with genital warts without anal condyloma should also undergo perianal examination for detection and treatment of subclinical lesions as a means of screening and prevention of anal cancer. Objectives: To determine the cytological findings of anal collection in patients with genital HPV. Methodology: cross-sectional, observational, descriptive study. We included patients with HPV-induced genital injury, or genital lesion without precancer with confirmed HPV infection or genital cancer who agreed to participate by signing the informed consent form. Discussion: Most patients were over 30 years of age, coming from the interior, average of three partners per woman, the main findings are condyloma and CIN 1. Most patients reported having had one to five preventives, were not alcoholics, smokers or even using condoms. Most are single. In anal cytology, the main findings were negative and koilocytosis. Conclusion: Most patients with cytological alterations have koilocytosis in addition to the most common findings being condyloma and CIN 1. Injuries still early and with great reversal potential.